Factors associated with occupational stress among nurses working in clinics in Gaborone,Botswana - Maphangela, Tabby (University of Limpopo, 2015)
The purpose of the study was to find out factors associated with occupational stress among nurses working in clinics in Gaborone. The study was conducted in Gaborone district targeting all primary healthcare clinics. The specific focus was drawn to all registered nurses working in clinics in Gaborone. The objective of the study was to investigate factors associated with occupational stress among nurses working in clinics in Gaborone. A quantitative study was carried out in this study. A sample of 106 respondents was used in the study. Purposive sampling was employed to select respondents that were included in the study. Data was collected through a self-administered questionnaire which comprised of close and open ended questions. Informed consent was obtained from the participants who participated in the study. The study revealed that a higher percentage (74%) of nurses have ever experienced occupational stress. The results also revealed that females 80 percent respondents experienced stress compared to their male counterparts. The results also show that all of the respondents mentioned that they had experienced stress related to work. Respondents also mentioned that work relationship, shortage of staff, and workload contribute to stress among the nurses. On the other hand, the results of the study also found that staff welfare issues also contribute to stress among the nurses. These include lack of recognition, no personal growth, lack of support and unfriendly work environment. From the results most of the respondents indicated that there are no interventions dealing with stress in the workplace therefore the study recommends that interventions in the workplace needs to be introduced to address occupational stress among the nurse. Furthermore there is a need to create wellness programs, reduce work overload and motivate staff by promotions and other means in order to increase level of job satisfaction.
Thesis ( MPH.) -- University of Limpopo, 2015
Keywords: Occupational stress; Nurses; Stress; Workload; Nurses -- Botswana -- Job stress; Clinical psychology